Analisis Pengukuran Kinerja Menggunakan Value For Money Pada Pemerintahan Kota Medan - Ramadani, Ad Dini Elhilal; Sari, Eka Nurmala; Gantino, Rilla (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
This research was conducted because in the implementation of the preparation of regional revenue and expenditure budgets (APBD) there is often a waste of budget and inappropriate use targets that should be felt by the general public, and are still not optimal, especially there is no system for determining budget figures and LRA realization so that there is an upward and downward trend in the Medan City Government budget realization report in 2017-2021. The purpose of this study is to determine and measure The performance of the Medan City Government uses the concept of value for money , namely the economic ratio, the efficiency ratio and the effectiveness ratio, and to find out and analyze the causes of the economic ratio in the less economical category. To find out and analyze the causes of the efficiency ratio in the less efficient and moderately efficient categories. To find out and analyze the causes of the effectiveness ratio in the quite effective category. The research method used is descriptive method with quantitative and qualitative data types. Data collection techniques in this study are documentation and interviews and are adjusted to Kepmdagri N0. 690.900-327 of 1996 concerning guidelines for the assessment of financial performance measurement. And data analysis techniques using quantitative descriptive analysis techniques. The results of the value for money on the Medan City Government in 2017-2021 have an economic ratio which has an average of 77.73% in the less economical category, which has decreased because the target for the Medan City Government expenditure has not been achieved. In terms of the efficient ratio which has an average of 95.32% in the less efficient category. And in terms of the effectiveness ratio which has an average of 85.89% in the quite effective category, where both of these ratios have decreased due to the less than optimal regional income that has not reached the target set by the Regional Government.